Fecal microbiota transplantation for recurrent Clostridium difficile infection in patients with solid organ transplants: an institutional experience and review of the literature. Issue 6 (31st July 2018) - Lin, Steven C.; Alonso, Carolyn D.; Moss, Alan C.
Abstract: Clostridium difficile, an anaerobic gram‐positive, spore‐forming bacillus, has become the most common cause of nosocomial infectious diarrhea, and is associated with increased mortality in all populations. Patients who have received solid organ transplants (SOT) are at increased risk of Clostridium difficile infection (CDI) and CDI recurrence (rCDI). This may be related to chronic immunosuppression, frequent antibiotic exposure, and increased or prolonged hospitalizations. Increased morbidity and mortality from CDI is well‐described in SOT patients. Conventional treatments for index and recurrent CDI include vancomycin and fidaxomicin. Fecal microbiota transplantation has emerged as an effective and safe alternative for treating rCDI in the general population. Reports of its safety in certain immunocompromised populations, such as those with inflammatory bowel disease, appear reassuring, but outcomes among SOT patients are less well known. Here, we summarize the experiences published to date on the treatment of rCDI with FMT in SOT patient, and also describe our detailed FMT protocol and experience in treating a series of SOT patients with rCDI. In addition to reporting the safety and efficacy of our FMT experience, we also discuss the diagnostic challenges and considerations in this population of solid organ transplant recipients.